Gut microbiota and vitamin status in persons with obesity: A key interplay. (12th November 2021) - Voland, Lise; Le Roy, Tiphaine; Debédat, Jean; Clément, Karine
Summary: There are numerous factors involved in obesity progression and maintenance including systemic low‐grade inflammation, adipose tissue dysfunction, or gut microbiota dysbiosis. Recently, a growing interest has arisen for vitamins' role in obesity and related disorders, both at the host and gut bacterial level. Indeed, vitamins are provided mostly by food, but some, from the B and K groups in particular, can be synthesized by the gut bacterial ecosystem and absorbed in the colon. Knowing that vitamin deficiency can alter many important cellular functions and lead to serious health issues, it is important to carefully monitor the vitamin status of patients with obesity and potentially already existing comorbidities as well as to examine the dysbiotic gut microbiota and thus potentially altered bacterial metabolism of vitamins. In this review, we examined both murine and human studies, to assess the prevalence of sub‐optimal levels of several vitamins in obesity and metabolic alterations. This review also examines the relationship between vitamins and the gut microbiota in terms of vitamin production and the modulation of the gut bacterial ecosystem in conditions of vitamin shortage or supplementation. Furthermore, some strategies to improve vitamin status of patients with severe obesity are proposed within this review.